Implications of the dominant imagery “Barrios del Sur” in the creation of urban space - Villalobos Vega, Roberto (2016)
The city and what is understood as its reality, is a complex and endless dynamic of territorial production between its imaginary dimension (memory, ideas, senses, emotions, etc.), empirical dimension (buildings, infrastructure, events), and how its citizens, civil society and those in power, amalgamate the different variables that compose it to symbolize and constantly build it (social dimension). Given this premise, this article outlines the media construction of the territory from the phenomenon of social representations “Barrios del Sur” as an urban issue, a dominant imaginary that designates the south part of Casco Central (Central Town: mainly Hospital and Catedral districts), in San José, Costa Rica, under negative assumptions and generalizations; and its profound impact on the city production in terms of territorial organization (location of fears and guilts in the city), urban planning, design, investment, and life.